Introduction to the papers of TWG21: Assessment in mathematics education - Paola Iannone; Michal Ayalon; Johannes Beck; Jeremy Hodgen; Francesca Morselli (2019)
TWG21 met for the second time in Utrecht at CERME11 and in this conference we sought to continue the work started at CERME10. The aim of the previous meeting was to ascertain where the interest of our community is when thinking about assessment, and to maintain the focus firmly on mathematics. At CERME11 we discussed 14 papers and 3 posters which helped defining such interest. We noticed again a variety of focal points: from validation of large-scale assessment instruments, to the affordances and drawbacks of online assessment – especially in the university context - to the details of construction of individualised feedback. As in the previous meeting the papers also presented a variety of methodologies: from large quantitative studies to more nuanced qualitative investigations. Among the submissions we also received papers related to students’ perspectives and teachers’ perspectives on assessment. These themes were not prominent in the past meeting of the group and we welcomed the new perspectives they brought. Finally, we decided to group papers together that indicated the role that mathematics has in the assessment: this is to say papers that focus on the specifics of mathematics, such as assessing proof.